Asymmetries in Volatility: An Empirical Study for the Peruvian Stock and Forex Market - Alanya, Willy (2016)
Symmetric and asymmetric autoregressive conditional heteroskedasticity models and stochastic volatility models are applied to daily data of Peruvian stock and Forex markets returns for the period January 5, 1998 until December 30, 2011. Following the approach developed by Omori et al. (2007), Bayesian estimation methodology is used with different structures in the behavior of the disturbance terms. The results suggest the presence of asymmetric effects in both markets. In the stock market, we find that negative shocks generate higher volatility than positive shocks. In the Forex market, shocks related to episodes of depreciation create higher uncertainty in comparison with episodes of appreciation. Thus, the Central Reserve Bank faces relatively major difficulties in its intention of smoothing Forex volatility. The model with the best fit in both returns is the Asymmetric Stochastic Volatility with Normal errors. The stock market returns have greater periods of volatility; however, both markets react to shocks in the economy, as they display similar patterns and have a significant correlation for the sample period studied. Modelos de volatilidad estocástica y modelos de heterocedasticidad condicional autorregresiva simétricos y asimétricos son aplicados a datos diarios de los retornos bursátiles y cambiarios peruanos para el período desde el 5 de Enero de 1998 hasta el 30 de Diciembre de 2011. Siguiendo el enfoque desarrollado por Omori et al. (2007), se usa metodología Bayesiana con diferentes estructuras en el comportamiento de los términos de perturbación. Los resultados sugieren la presencia de efectos asimétricos en ambos mercados. En el mercado de valores, encontramos que los choques negativos generan una mayor volatilidad que los choques positivos. En el mercado cambiario, los choques relacionados con episodios de depreciación crean mayor incertidumbre en comparación con episodios de apreciación. Por lo tanto, en este caso, el Banco Central de Reserva del Perú enfrenta relativamente mayores dificultades en su intención de suavizar la volatilidad del tipo de cambio. El modelo con el mejor ajuste en ambos rendimientos es el modelo de volatilidad estocástica asimétrico con errores normales. Los rendimientos del mercado de valores tienen mayores períodos de volatilidad; sin embargo, los mercados reaccionan a las perturbaciones en la economía, ya que muestran patrones similares y tienen una correlación significativa para el período de la muestra estudiada.